Does a generous welfare state crowd out student effort? Panel data evidence from international student tests - Torberg Falch; Justina A. V. Fischer (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
Student achievement has been identified as an important contributor to economic growth. This paper investigates the hypothesis that redistributive government activities have a negative effect on investment in human capital using data from international comparative student achievement tests in Mathematics and Science for over 70 countries during the period 1980 to 2003. In fixed effects models, both the effects of government consumption and government social expenditures on student achievement are negative and seem to be robust across different model specifications. The effect of social expenditures appears to be driven by spending on pensions and active labor market policies.
Keywords: C33; H20; I20; 330; achievement; welfare state; panel data; PISA; TIMSS; Sozialstaat; Studierende; Bildungsniveau; Welt; OECD-Staaten